The relationship between service quality, customer satisfaction, and hedonic value on generation Y customer loyalty in the context of superstores in Bangladesh: the mediating role of corporate image - Alam, Mirza Mohammad Didarul (2020)
With the face of immense competition, today's retailers are struggling more to retain their existing customers. This scenario is even worse in the superstore sector in Bangladesh particularly who are dealing with Generation Y customers. Inherently, Generation Y customers exhibit less loyalty but offer themselves as a lucrative market segment. Due to their unique characteristic, attracting and retaining this young cohort is inevitable for the superstore owners. Hence, this study aimed to identify the factors influencing the loyalty of Generation Y customers in the superstore context of Bangladesh. The objective of this study was to investigate the relationships between service quality, customer satisfaction, hedonic value, corporate image, and customer loyalty of Generation Y. This study also examined the mediating role of corporate image on the relationship of service quality, customer satisfaction, and hedonic value with customer loyalty of Generation Y aligned with the Stimulus-Organism-Response (S-0-R) paradigm. By following the cross-sectional research design, a survey was conducted. Data was collected from 340 Generation Y customers who visited four leading superstores in Bangladesh, namely Agora, Meenabazar, Princebazar, and Shwapno. Partial Least Squares - Structural Equation Modeling (PLS-SEM) was utilized to confirm the reliability and validity of the measurement model and to test the significance of the hypothesized relationships. The outcomes of the structural model revealed that service quality, customer satisfaction, hedonic value, and corporate image have a significant direct effect on customer loyalty. In addition, corporate image was significantly affected by service quality, customer satisfaction, and hedonic value. Furthermore, the findings of this study confirmed the indirect effect of service quality, customer satisfaction, and hedonic value on customer loyalty through corporate image. This study also provides theoretical, methodological, and practical contributions for the academics and professionals. Finally, with the acknowledgement of limitations, this study offers some recommendations for future study.